KARAKTERISTIK MOTIF TENUN OMAH PETROK DI DESA TROSO JEPARA - Fajarena, Yustia; Yustana, Prima (Institut Seni Indonesia Surakarta, 2022)
Ikat weaving is one of the noble heritages in the form of cloth or textiles which until now has been in great demand by the people of Indonesia. Weaving is used as a symbol of dress by certain communities. This study aims to describe the historical background of omah petrok weaving in Torso Jepara Village, explain the creative process of omah petrok weaving for the people of Torso Village, outline the forms and meanings contained in the Omah Petrok woven cloth used by the people of Troso Jepara Village. This research is a qualitative research. The subject of this research is Omah Petrok's woven fabric in Troso Jepara Village. In addition, data obtained from observation techniques, interviews and documentation. Data analysis was also carried out in a qualitative descriptive manner with the steps of data collection, data reduction, data processing, data testing, and drawing conclusions or verification. The research location is on Jl. Datuk Ampel Troso Village 01/02 Pecangaan Jepara. The results of this study are to determine the home industry that produces weaving, namely Omah Petrok Weaving, to determine the production potential of the home industry. The technique for making Omah Petrok Weaving includes: selecting materials and tools, making weaving designs, choosing colors based on themes, coloring processes, weaving and finishing processes. As well as explaining the meaning of the omah petrok woven motif and the uses of the omah petruk woven motif.